Effects of Replacing Peanut Seed Cake with Brewery Dried Yeast on Laying Performance, Egg Quality and Carcass Characteristics of Rhode Island Red Chicken - Girma, Meseret; Tamir, Berhan; Dessie, Tadelle (International Journal of Poultry Science, 2011)
One hundred and eighty 26-week old Rhode Island Red chicken were used to determine the performance, fertility, hatchability and economic of chicken fed with ration containing Peanut Seed Cake (PSC) and Brewery Dried Yeast (BDY). The treatments were T1 (20% PSC + 0% BDY), T2 (15% PSC + 5% BDY), T3 (10% PSC + 10% BDY), T4 (5% PSC + 15% BDY), T5 (0% PSC + 20% BDY) and T6 as control (commercial layer’s ration) and the experiment lasted for 12 weeks. The experiment was arranged in a Completely Randomized Design (CRD) with six treatments, each replicated two times with 15 birds per replicate. Hens were individually weighed at the start and end of the experiment. Data on Dry Matter Intake (DMI), Hen Day Egg Production (HDEP), egg weight and were recorded daily. Egg quality parameters were determined at an interval of 3 days on 6 eggs per replicate. The chemical analysis showed that BDY contained 41.2% CP and 2982.04 kcal ME/kg DM and PSC 42.2% CP and 2842.5 kcal ME/kg DM, indicating their potential to be used as sources of both protein and energy in poultry feeding. DMI of birds on T3 and T4 were similar with that of birds on control diet, but diet T5 resulted in significantly increased DMI than control diet. Diets T1 and T2 resulted in a significantly (p<0.05) decreased DMI than control diet. Final body weight and body weight gain of birds was significantly lower (p<0.05) for T1 and T2 than that of birds on T4. Birds on T3 had higher HDEP compared to birds on control ration. Diet containing T4 resulted in a significant increase (p<0.05) in egg weight than that of birds on T2 and control diet but the diet containing T1 resulted in a significantly decreased (p<0.05) egg weight than control diet and other treatment groups. Birds on T4, T5, T3 and T2 showed better results in fertility than control and T1. Similarly birds in T2, T3, T4 and T5 were better in hatchability than the birds in control and T1. Eggs of birds on T3, T4 and T5 showed higher yolk color value than birds on control diet. Birds of treatment T3 had lower feed cost per dozen of egg than control, indicating the importance of this form of combination for feeding layers as least cost ration than that of the birds on control. The results also showed that initial body weight, feed efficiency, albumen height in terms of Haugh unit, shell thickness and egg sale to feed cost ratio did not vary (p>0.05) among dietary treatments. Brewery dried yeast could be included in Rhode Island Red chicken feed in order to increase fertility and hatchability of fertile eggs, yolk color and it also increase egg mass. Based on the results of this study, T3 (10% BDY + 10% PSC) or 50% replacement of BDY by PSC appeared to be a diet of good feeding value, more economical or reasonably cheaper ration which can be used as protein supplement in formulation of layers ration without adverse effects on egg laying performance of pullets between 26-38 weeks of age.